Adaptive Markets Hypothesis: A Systematic Review of Its Testing and Application in Financial Market Efficiensy Studies - Muhdsan, Mudhia'ah; Maharani, Dewi Shintya; Indrijawati, Aini; Ferdiansah, Muhammad Irdam (Muhasabatuna : Jurnal Akuntansi Syariah, 2025)
This study is a Systematic Literature Review (SLR) that aims to examine how the Adaptive Markets Hypothesis (AMH) has been tested and applied in studies on financial market efficiency. Through a systematic selection process, 30 scientific articles from reputable Scopus journals (Q1 and Q2) have been analyzed to answer five main research questions, including the AMH testing approach, the methodology used, the type of market or instrument studied, the results of empirical studies, and the limitations and directions of further research. The review results show that most studies provide support for the AMH, with the finding that market efficiency is dynamic (time-varying) and can change depending on crises, economic conditions, and investor behavior. The AMH has been tested on various markets such as stocks, foreign exchange, commodities, and crypto, both in developed and developing countries. The methodological approaches used are also diverse, ranging from rolling window analysis, variance ratio test, Hurst exponent, to machine learning-based methods and Bayesian inference. This SLR concludes that the AMH offers a more realistic framework than the Efficient Market Hypothesis (EMH), especially in understanding the efficiency of modern complex and adaptive markets. This study makes theoretical and practical contributions, and recommends that further research develop the AMH approach in under-researched market contexts and with more innovative analytical methods.